2018
DOI: 10.1161/circulationaha.117.030501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Distinct Lifestyle Interventions on Mobilization of Fat Storage Pools

Abstract: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01530724.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
214
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(229 citation statements)
references
References 50 publications
6
214
0
9
Order By: Relevance
“…Another longer trial found that subjects following a low‐carbohydrate MD had a greater reduction in HS than those following a low‐fat diet. However, the absolute magnitude of this difference was small (1.5%) . The significant caloric restriction, very low carbohydrate intake in the Mediterranean arm, greater weight loss, and inclusion criteria (only one half of subjects had NAFLD) are all meaningful differences from our trial.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Another longer trial found that subjects following a low‐carbohydrate MD had a greater reduction in HS than those following a low‐fat diet. However, the absolute magnitude of this difference was small (1.5%) . The significant caloric restriction, very low carbohydrate intake in the Mediterranean arm, greater weight loss, and inclusion criteria (only one half of subjects had NAFLD) are all meaningful differences from our trial.…”
Section: Discussionmentioning
confidence: 67%
“…However, the absolute magnitude of this difference was small (1.5%). (43) The significant caloric restriction, very low carbohydrate intake in the Mediterranean arm, greater weight loss, and inclusion criteria (only one half of subjects had NAFLD) are all meaningful differences from our trial. Importantly, our trial established the ability of subjects to achieve nutrient intakes comparable to documented traditional Mediterranean diets.…”
Section: Discussionmentioning
confidence: 70%
“…9,16 The CENTRAL-MRI trial demonstrated that in a group of 278 sedentary adults (age = 48 years, 89% men, BMI 30.8 kg/m 2 ) with abdominal obesity (75%) or dyslipidemia, a Mediterranean lowcarbohydrate dietary pattern was superior to a low-fat diet in decreasing intrahepatic, intrapericardial, and pancreatic fat (P < 0.05 for all), and that exercise had an independent contribution to visceral AT loss. 27 Further to that, mobilization of ectopic fat depots was associated with improved cardiometabolic surrogate markers such as decreased expression of atherogenic dyslipidemia. 27,28 Skeletal muscle secretome.…”
Section: An Integrative View On Atherosclerosismentioning
confidence: 96%
“…is a secondary analysis of a large randomised clinical trial (RCT) (CENTRAL RCT), testing long-term dietary interventions with or without physical activity. 1 The current analysis focused on the possible role of liver fat in mediating the improvement in cardiovascular disease (CVD) risk factors induced by the Mediterranean diet (MD). Indeed, it has been well established that the MD improves insulin sensitivity and features of the metabolic syndrome 2,6 and reduces the incidence of CVD outcomes in both observational studies and RCTs.…”
mentioning
confidence: 99%
“…9,10 Support for these findings is needed from longer-term trials, such as the 18-month CEN-TRAL RCT. 1 Gepner et al have made an excellent attempt to clarify the mechanisms by which the MD achieves the observed CVD risk reduction. They have demonstrated that the MD combined with a low carbohydrate (LC) diet conferred a reduction in hepatic fat, which was associated with improvements in surrogate measures of CVD risk, beyond those seen with visceral fat loss.…”
mentioning
confidence: 99%